RASIO LIDAH BUAYA DAN RUMPUT LAUT TERHADAP MUTU PERMEN JELLY - Fina Fitrina; Akhyar Ali; Shanti Fitriani (Jurnal Sagu, 2014)
Jelly candy is one from of diversification of products aloe vera and seaweed. This study aims to get the right ratiobetween aloe vera and seaweed to produce jelly candies with good quality. Parameters observed in this studymoisture content, ash content, pH, reducing sugar content, crude fiber content and organoleptic testing the level ofpreference panelist on candy jelly with aloe vera and the ratio of seaweed. The study was conducted using acompletely randomized design with 3 (three) replications consisting of 5 (five) treatments are:LR1 (aloe vera 90% :10% seaweed), LR2 (aloe vera 80% : 20% seaweed), LR3 (aloe vera 70% : 30% seaweed), LR4 (aloe vera 60% :40% seaweed), and LR5 (aloe vera 50% : 50% seaweed). The result of analysis showed that the ratio of aloe veraand seaweed significantly effect on moisture content, ash content, reducing sugar content, and crude fiber contentand not significantly effecton pH and the overall ratio of aloe vera and seaweed preferred by the panelists. Theratio of aloe vera and seaweed in the treatment LR4 (aloe vera 60%:40% seaweed) is best treated with a moisturecontent of 16.44%, ash content 0.38%, pH 3.36, reducing sugar content 22.62%, crude fiber content of 1.44% andpreferred by the panelists in organoleptic testing.Key words: Aloe vera, seaweed, jelly candy